Sistem Pendukung Keputusan Pemilihan Sekolah SMA Swasta Terbaik Dengan Menggunakan Metode PROMETHEE Di Kota Pematangsiantar - Yuni Arista Saragih; Jaya Tata Hardinata; Muhammad Ridwan Lubis (LPPM STIKOM Tunas Bangsa, 2019)
Selection of the best private schools in embassy cities with the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) method. This decision support system is built through 6 stages. The first stage is collecting data and information through interviews and document analysis. The second stage is processing data and information to get the system design to be built. The third stage is system analysis which includes school data input, weighting criteria with the PROMETHEE method, and alternative ranking with the PROMETHEE method. The Fourth stage is designing the system using the concept of Object Oriented Design. The fifih stage is the implementation of a web-based system. The last step is evaluating the system by comparing the level of accuracy between the PROMETHEE method. With the implementation of the PROMETHEE method for the selection of the best private schools that will result in the ranking of the best private schools, it is expected that in the selection of the best schools that are truly recommended in accordance with the wishes and abilities of students